Mangrove Estimasi Stok Karbon Pada Tegakan Mangrove Di Desa Sukamandi Kabupaten Belitung Timur - Sapriyadi Sapriyadi; Arthur M. Farhaby; Sudirman Adibrata (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Sukamandi is a village located in East Belitung Regency which has a mangrove ecosystem area of 351.33 ha. Mangrove ecosystems play an important role in carbon sequestration as one of the blue carbon concepts. This study aims to analyze the type and density of mangroves and to analyze the value of aboveground biomass and the value of carbon stock in mangrove stands in Sukamandi Village, East Belitung Regency. This research was conducted in January-February 2023 in the Mangrove Forest of Sukamandi Village, East Belitung. Analysis of the value of biomass and carbon stock was carried out based on SNI 7724 of 2011. The results of the research that had been carried out were 5 mangrove tribes consisting of 10 species with the highest density of mangrove vegetation types at station III, which was 4,841 ind/ha and the lowest at station IV, namely 1,943 ind/ha with Very Dense criteria. The average value of standing mangrove biomass is 509.34 tons/ha, the average value of carbon stock in mangrove stands is 239.39 tons/ha. Keywords: Mangrove Stand, Biomass, Carbon Stock, Sukamandi Village